Prediksi Kejadian Penyakit Tuberkulosis Paru Berdasarkan Jenis Kelamin - Sri Andayani (Fakultas Ilmu Kesehatan, Universitas Muhammadiyah Bengkulu, 2020)
Tuberculosis (TBC) is a case that is always increasing every year. Assessment of progress and success of pulmonary tuberculosis control in Ponorogo Regency uses indicators of suspicion screening numbers with health promotion, especially pulmonary TB. The purpose of this study was to analyze the prediction of the incidence of pulmonary tuberculosis based on gender in Ponorogo Regency from 2016 to 2020. This research is a quantitative descriptive study using a cross-sectional design with time series analysis approach with trend method. The population and sample in this study were all data on cases of smear positive lung tuberculosis which included the sex of the patient during 2011-2015 in Ponorogo Regency. Research Results The distribution of smear positive lung TB cases in the period 2011-2015 tended to increase with the number of cases respectively 276, 392, 378, 293 and 334 cases. After predicting, pulmonary TB cases in 2016-2020 will decline with cases of 299, 348, 366, 352, and 306 respectively.Based on the results of time series analysis with the trend method based on gender in Ponorogo Regency in 2016-2020, It is predicted that pulmonary TB cases will continue to increase and it is estimated that in 2018 the highest number of cases is male with 222 cases, and female sex with 141 cases. In conclusion, there has been an increase in cases of pulmonary tuberculosis in men in 2018.Keywords: Incidence Prediction, TB, Gender